Current Antimicrobial Stewardship Practice and Education in Russian Hospitals: Results of a Multicenter Survey - Ivan Palagin; Svetlana Rachina; Marina Sukhorukova; Irina Nizhegorodtseva; Ulyana Portnyagina; Svetlana Gordeeva; Elena Burasova; Vladimir Bagin; Olga Domanskaya; Dilip Nathwani; Roman Kozlov (Antibiotics, 2021)
Proper antibiotic usage education and training of medical students and healthcare professionals is the cornerstone to implement antimicrobial stewardship (AMS) programs worldwide. We conducted this voluntary and anonymous survey on current and preferred educational provision of AMS in Russia. Among 1358 polled respondents from six participating Centers located in geographically remote Federal Districts of Russia, the majority were nurses (52.8%) and doctors (42.0%). Results of the survey demonstrated better coverage of education in AMS on an undergraduate level (57.1%). More than half of respondents in total (52.4%) stated they had not received any postgraduate training. Those 38.4% respondents who received postgraduate teaching in AMS stated that it had been provided substantially by an employing hospital (28.4%) or by a medical university/college (22.3%). According to the conducted survey, the methods of education in AMS in Russian Federation mainly include traditional face-to-face lectures, presentations and provision with clinical guidelines, recommendations and printed materials. The involvement of e-learning and web-based online approaches was lacking. The survey allowed us the identify the key problems associated with training of healthcare workers in this field, in particular the varying availability of under- and postgraduate education in different parts of Russia.